2014
DOI: 10.1371/journal.pone.0085423
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of the Bovine Rumen Microbiome in Modulating Milk Composition and Feed Efficiency

Abstract: Ruminants are completely dependent on their microbiota for feed digestion and consequently, their viability. It is therefore tempting to hypothesize a connection between the composition and abundance of resident rumen bacterial taxa and the physiological parameters of the host. Using a pyrosequencing approach, we characterized the rumen bacterial community composition in 15 dairy cows and their physiological parameters. We analyzed the degree of divergence between the different animals and found that some phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
379
8
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(440 citation statements)
references
References 27 publications
46
379
8
7
Order By: Relevance
“…The composition of the core rumen microbiome did not change, but the relative abundance of these two phyla showed great variation, since the percentage of Bacteroidetes was less than Firmicutes. Bacteroidetes and Firmicutes are the most prevalent phyla in many ruminants, and the Firmicutes to Bacteroidetes ratio has been considered as an important parameter for assessing the microbe impact on host energy requirements [33,40,75]. Many studies have found a strong correlation between the ratio of Firmicutes to Bacteroidetes related to roughage proportion and milk-fat yield [19,33,57].…”
Section: Core Prokaryotic Communities In the Rumenmentioning
confidence: 99%
See 2 more Smart Citations
“…The composition of the core rumen microbiome did not change, but the relative abundance of these two phyla showed great variation, since the percentage of Bacteroidetes was less than Firmicutes. Bacteroidetes and Firmicutes are the most prevalent phyla in many ruminants, and the Firmicutes to Bacteroidetes ratio has been considered as an important parameter for assessing the microbe impact on host energy requirements [33,40,75]. Many studies have found a strong correlation between the ratio of Firmicutes to Bacteroidetes related to roughage proportion and milk-fat yield [19,33,57].…”
Section: Core Prokaryotic Communities In the Rumenmentioning
confidence: 99%
“…Bacteroidetes and Firmicutes are the most prevalent phyla in many ruminants, and the Firmicutes to Bacteroidetes ratio has been considered as an important parameter for assessing the microbe impact on host energy requirements [33,40,75]. Many studies have found a strong correlation between the ratio of Firmicutes to Bacteroidetes related to roughage proportion and milk-fat yield [19,33,57]. Jami et al [30] found that Bacteroidetes was more abundant than Firmicutes in older bovines that had a diet composed mainly of plant fiber, but they were less abundant in newborns.…”
Section: Core Prokaryotic Communities In the Rumenmentioning
confidence: 99%
See 1 more Smart Citation
“…Feed efficiency in dairy cattle is known to be affected by a variety of factors, including host genetics, environmental conditions such as ambient temperature, the various metabolic contributions and demands of pregnancy, tissue mobilization, and immune response. Moreover, recent studies have reported that the composition of the ruminal microbial community is associated with differences in several drivers of feed efficiency (2, 12-15), milk yield and composition (12,(16)(17)(18)(19), and alterations in pregnancy stage (20).Recent work using high-throughput sequencing technology has revealed correlations between the abundance of particular ruminal bacterial genera with milk composition and RFI, although these determinations did not consider changes over entire lactation cycles (12,20). Given that milk production is altered by major physiological shifts associated with stage of lactation and pregnancy (6, 21), it is necessary to consider that time may be a significant variable in the composition of the ruminal microbial community.…”
mentioning
confidence: 99%
“…Previous studies of the rumen microbiome from steers found that changes in the abundances of microbial population were associated with feed efficiency group 3,4,18 . However, in vivo microbial communities composition associated with changes in biohydrogenation have had low correlation 19,20 and limited explanation of it association 21 .…”
Section: Discussionmentioning
confidence: 95%